Multiscale analysis of cohesive fluidization - Umoh, Utibe Godwin (The University of Edinburgh, 2018)
Fluidization of a granular assembly of solid particles is a process where particles are suspended in a fluid by the upward flow of fluid through the bed. This process is important in industry as it has a wide range of applications due to the high mixing and mass transfer rates present as a result of the rapid movement of particles which occurs in the bed. The dynamics of fluidization is heavily dependent on the particle scale physics and the forces acting at a particle level. For particles with sizes and densities less than 100μm and 103 kg/m3, the importance of interparticle forces such as cohesion to the fluidization phenomena observed increases compared to larger particles where phenomena observed are more dependent on hydrodynamic forces. These smaller sized particles are increasingly in high demand in industrial processes due to the increasing surface area per unit volume obtained by decreasing the particle size. Decreasing particle however leads to an increase in the impact of cohesive interparticle forces present between particles thus altering fluidization phenomena. It is thus necessary to get a greater understanding of how these cohesive forces alter fluidization behaviour both at the particle and also at the bulk scale. This work begins with an experimental study of a fluidized bed using high speed imaging. The applicability of particle image velocimetry for a dense bed is examined with verification and validation studies showing that particle image velocimetry is able to accurately capture averaged velocity profiles for particles at the front wall. A digital image analysis algorithm which is capable of accurately extracting particle solid fraction data for a dense bed at non-optimum lighting conditions was also developed. Together both experimental techniques were used to extract averaged particle mass flux data capable of accurately capturing and probing fluidization phenomena for a dense fluidized bed. This simulation studies carried out for this work looks to examine the impact of cohesive forces introduced using a van der waal cohesion model on phenomena observed at different length scales using DEM-CFD simulations. Numerical simulations were run for Geldart A sized particles at different cohesion levels represented by the bond number and at different inlet gas velocities encompassing the different regimes fluidization regimes present. A stress analysis was used to examine the mechanical state of the expanded bed at different cohesion levels with the vertical component of the total stress showing negative tensile stresses observed at the center of the bed. Further analysis of the contact and cohesive components of the stress together with a kcore and microstructural analysis focusing on the solid fraction and coordination number profiles indicated that this negative total stress was caused by a decrease in the contact stress due to breakage of mechanical contacts as cohesive forces are introduced and increased. A pressure overshoot analysis was also conducted with the magnitude of the overshoot in pressure seen during the pressure drop analysis of a cohesive bed shown to be of equivalent magnitude to the gradient of the total negative stress profile. The in-homogeneous nature of the bed was probed with the focus on how introducing cohesion levels increase the degree of inhomogeneity present in the expanded bed and how local mesoscopic structures change with cohesion and gas velocity. It was shown that increasing cohesion increases the degree of inhomogeneity in the bed as well as increasing the degree of clustering between particles. A majority of particles were shown to be present in a single macroscopic cluster in the mechanical network with distinct local mesoscopic structures forming within the macroscopic cluster. The cohesive bed also expanded as distinct dense regions with low mechanical contact zones in between these regions. A macroscopic cluster analysis showed that the majority of particles are in strong enduring mechanical and cohesive contact. Increasing cohesive forces were also shown to not only create a cohesive support network around the mechanical network but also strengthen the mechanical contact network as well. The significance of the strong and weak mechanical and cohesive forces on fluidization phenomena was also examined with analysis showing that the weak mechanical forces act to support the weak mechanical forces. The cohesive force network however was non coherent with strong forces significantly greater than weak forces. Fluidization phenomena was shown to be driven by the magnitude of the strong cohesive forces set by the minimum particle cutoff distance. This also called into question the significance of the cohesive coordination number which is dependent on the maximum cohesive cutoff. The value of the maximum cutoff was shown to be less significant as no significant changes were observed in the stress and microstructure data as the maximum cutoff was altered. Simulations with different ratios of cohesive and non cohesive particles were also undertaken and showed that a disruption in the cohesive force network leads to changes in the stress state and microstructure of the bed thus changing the fluidization phenomena observed at all length scales. The nature of the strong cohesive force network thus drives fluidization phenomena seen in the bed.
Keywords: fluidization; cohesion; numerical simulations; optimization; high speed imaging; digital image analysis algorithm